Optimizing the Use of Artificial Intelligence in Accelerating the Implementation of the Indonesian Judicial Reform Blue Print 2035 - Andi Hakim Lubis; Serimin Pinem; Tommy Aditya Sinulingga; Mhd. Hasbi; Fahrizal S. Siagian; Misael Andry Ariffando Sinaga (Universitas Muhammadiyah Surakarta, 2024)
One of the real problems in the judicial institution is the lack of quantity of human resources or the number of judges assigned to judicial institutions or the Supreme Court to handle cases. The shortage of human resources or the number of judges is a serious problem and should not be considered a naive matter. This is because, according to the author, the shortage of judges has the potential to produce new injustices and also become a new problem in reality. If the shortage of judges is ignored and there is no effort to immediately find a solution, it is feared that it will result in the low quality of judges' decisions. This is because the number of cases that will be worked on by judges will certainly drain a lot of energy and thoughts. This means that if it is true that the judiciary has been short of judges, this should be equivalent to an excess of judges' duties to cover case handling. One of the efforts made is the use of technology in supporting the workload in the judicial institution and the supreme court is a necessity and part of the acceleration of the manifestation of the blueprint (blue print) of Indonesian Judicial Reform 2010-2035. This research is normative research. research conducted by examining the literature by taking a statute approach. The urgency of utilizing Artificial Intelligence cannot be separated from the development of advanced technology and its necessity in supporting the completion of the workload of the judicial institution and the Supreme Court. Therefore, optimizing the use of technology, especially Artificial Intelligence, must be able to accelerate the realization of the 2010-2035 Indonesian Judicial Reform blueprint.